Answer:
Option E) [tex]\frac{b}{3}+3[/tex] is correct
The expression which represents the sum of c and 3 in terms of b is
[tex]\frac{b}{3}+3[/tex]
Step-by-step explanation:
Given that b and c are real numbers such that
the product of c and 3 is b
That is given by (c)(3)=b
3c=b
To find the expression which represents the sum of c and 3 in terms of b:
the sum of c and 3 =c+3
From given 3c=b
[tex]c=\frac{b}{3}[/tex]
Now substitute the value [tex]c=\frac{b}{3}[/tex] in c+3 we get
[tex]c+3=\frac{b}{3}+3[/tex] which represents in terms of b
Therefore the expression which represents the sum of c and 3 in terms of b is [tex]\frac{b}{3}+3[/tex]
Therefore option E) [tex]\frac{b}{3}+3[/tex] is correct